Design Low Noise Digital Decimation Filter For Sigma-Delta-ADC - Kanika Sharma, Pramod Kumar Singh, (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper focuses on the design of digital decimation filter for single bit Sigma-DeltaA/Dconverter with medium oversampling ratio for the processing of audio and biomedical signal. Asecond-order single-stage sigma-delta (Σ-Δ) modulator with single bit quantizer with oversampling ratio96 workas a basic modulator. For hardware requirement, multiplier less CIC compensation FIR filterarchitectureused. Total three CIC compensation filter are used for decimation and filtering purpose. Allfilters are designed and simulated with MATLAB